Developments in granting economic real estate for investment are a challenge to eliminating bureaucracy and providing real support for the implementation of investment projects. - benlameur, walid; sonia, makri (The journal of Teacher Researcher of Legal and political Studies, 2025)
Previous practices in Algeria, particularly in attracting investments, particularly foreign ones, have had many negative effects, leading to widespread bureaucracy and the failure to complete investment projects as required. This has also led to increased investor concerns about their investment activities, prompting the Algerian government to adopt a rational Policy of seeking the most effective methods and resources to attract investment and address the biggest obstacles facing investment, particularly with regard to the issue of providing real estate for investment projects. This was embodied in Law 23/17, which defines the conditions and procedures for granting economic real estate belonging to the state's private property, intended for the implementation of investment projects. This research aims to identify the new developments introduced by Law 23/17 related to economic real estate, which is considered a gain in eliminating bureaucracy and embodying a digital system in organizing the granting of economic real estate, ensuring real support for investors, as well as the provisions for granting concessions and deciding to convert concessions into concessions for the exploitation of economic real estate, ensuring the elimination of concerns facing investors regarding their investment activities on the one hand, and achieving the state's development goals on the other hand